Structure elucidation and antitumor activity of a water soluble polysaccharide from Hemicentrotus pulcherrimus. (15th September 2022) - Jiang, Yan; Shang, Zhipeng; Lv, Xinyue; Du, Min; Ma, Li; Hou, Guige; Chen, Jing; Wang, Chunhua; Zhao, Feng
Abstract: Sea urchin nowadays serves as a delicacy around the world, and its gonads accumulate abundant polysaccharides before gametogenesis. However, the structure and bioactivity of these polysaccharides remain less well understood. Herein, a water soluble polysaccharide (HPP-1S) with a molecular weight of 2.996 × 10 7  Da was purified from the gonads of Hemicentrotus pulcherrimus . Chemical, spectroscopic and oligosaccharide sequencing analyses revealed that HPP-1S was a highly homogeneous polysaccharide featuring a linear backbone of 1, 4-linked α-d -glucose with 1, 6-α-d -glucose and 1, 6-α-D -glucuronic acid side chains grafted on the backbone in an alternating pattern. In vitro, HPP-1S can arrest the cell cycle at G2/M and sub-G1 phases, and induce apoptosis in Hela cells potentially by increasing expression ratio of Bax/Bcl-2. In vivo, HPP-1S exhibited obvious antitumor efficacy in Hela xenograft-bearing nude mice with low toxicity. These findings indicated that HPP-1S might serve as a potential low toxic antitumor agent. Highlights: A new polysaccharide HPP-1S was isolated from Hemicentrotus pulcherrimus gonads. The structure of HPP-1S was characterized by spectroscopic and oligosaccharide sequencing analyses. HPP-1S features a glucan backbone with Glc and GlcA branches. HPP-1S could induce apoptosis in Hela cells potentially via bax/bcl-2 pathway. HPP-1S exhibited antitumor efficacy in Hela xenograft-bearing nude mice.